Assessment of semantic memory in mild cognitive impairment: The psychometric properties of a novel semantic battery. Issue 4 (4th July 2022) - Ohman, Avery; Sheppard, Christine; Monetta, Laura; Taler, Vanessa
Abstract: Semantic memory is stable in healthy older adults but shows decline in mild cognitive impairment (MCI). Current measures of semantic function do not assess multiple aspects of semantic function and/or are time-consuming to administer. Here we report the psychometric properties of a battery to detect semantic impairment that we recently developed and published. Study 1 determined the face validity of the battery; interviews were conducted with five professionals with expertise in MCI and language. Face validity interviews suggested the battery appropriately assesses semantic impairments. Study 2 assessed convergent validity and reliability (inter-rater reliability, test-retest reliability, and internal consistency). Participants included 102 healthy older adults and 60 people with MCI who completed a four-task semantic battery. Results demonstrate that performance on the semantic battery correlates with traditional measures of semantic function, inter-rater reliability and internal consistency was high, and there was no significant change in mean scores between participants' first and second testing sessions. The present findings suggest that the semantic battery is a reliable and valid assessment of semantic function. It is currently recommended for research use only.